Mirna-mediated silencing of β-Secretase 1 (base 1): perspectives to a therapeutic approach to Alzheimer disease - Aristizábal, David; Hernández, Isarael; Lópera, Jaime; Boudreau, Ryan; Gallego Gómez, Juan Carlos; Cardona Gómez, Gloria Patricia (Iatreia, 2005)
Alzheimer's disease (AD) is characterized by two cerebral lesions associated to its phatology: amyloid plaques (<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:595.3pt 841.9pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->β-amyloid aggregates) and neurofibrillar tangles (Tau protein aggregates).